Prenatal diagnosis of the rare association of common arterial trunk and double aortic arch. Issue 7 (2nd June 2016) - Rock, Andrea; Eltayeb, Osama; Camarda, Joseph; Gotteiner, Nina
Key Clinical Message: Common arterial trunk with associated double aortic arch is a very rare constellation of congenital heart disease. Prenatal diagnosis allows for surgical repair prior to development of respiratory morbidity, which is otherwise described in all cases with this association. Abstract : Common arterial trunk with associated double aortic arch is a very rare constellation of congenital heart disease. Prenatal diagnosis allows for surgical repair prior to development of respiratory morbidity, which is otherwise described in all cases with this association.